PENGARUH LAYANAN PENGUASAAN KONTEN MENGGUNAKAN TEKNIK MEDIA AUDIO VISUAL TERHADAP MOTIVASI BELAJAR SISWA KELAS VIII DI SMP NEGERI 6 KOTA BENGKULU - ZAIMI SAPUTRA (Guidance and counseling the university of Prof. Dr. Hazairin. SH, 2017)
ABSTRACT This study aims to determine: (1) the level of students' motivation in class VIII SMP Negeri 6 Cities bengkulu before(pretest)provides services for mastery of content using audio-visual media techniques. (2) the level of students' motivation in class VIII SMP Negeri 6 of Bengkulu after(posttest)provides services for mastery of content using audio-visual media techniques. (3) whether there is an influence of mastery of content services using audio-visual media techniques on the students motivation in class VIII SMP 6 Bengkulu City. The method used in this study an experimental method in the form of one group pretest-posttest. The population in this study all students of class VIII SMP Negeri 6 Bengkulu city, amounting to 178 students. Samples were determined by purposive sampling technique consists of 24 students. Data analysis techniques used in this research method using the non-parametrictest Wilcoxon utilizing SPSS 20. The findings of this study show that: (1) The level of student motivation G class VIII SMP N 6 Bengkulu City before being given a mastery of content services using the technique of audio media there are two students visually very low category, 11 students category of low, medium category 8 students, 3 students of high category and there are no categories of students are very high. (2) The level of motivation of students of class VIII G SMP N 6 Cities Bengulu after a given service mastery of content using the technique of audio-visual media, increasing to very high category 4 students, a high category 11 students, a category was 9 students, and there are low or very low category. (3) There is a significant influence mastery of content services using audio-visual media techniques to motivate students of class VIII SMP Negeri 6 G in Bengkulu City. Keywords: Content Control Service, Audio Visual Media, and Motivation